Evaluation of Disclusion Time in Various Angle’s Malocclusions by T-Scan III System - Chutchalermpan, Titirat; Pumklin, Jittima; Piyapattamin, Thosapol (European Journal of Dentistry, 2019)
Objective The main purpose of this article is to evaluate the disclusion time (DT) in the lateral excursions and protrusion among subjects with Angle’s malocclusions using a T-Scan III system.Materials and Methods One hundred subjects with malocclusions were divided into Class I, Class II division 1, Class II division 2, and Class III (n = 25 per group). All groups’ DT of each excursion was evaluated by a T-Scan III system.Statistical Analysis One-way analysis of variance, followed by a post hoc test, was used to analyze the numerical data at p < 0.05.Results In the respective malocclusions, means ± standard deviations in second(s) of the DT were 2.08 ± 0.65, 2.13 ± 0.74, 2.12 ± 0.72, and 3.19 ± 1.34 during left excursion; 2.15 ± 0.94, 2.58 ± 1.16, 2.37 ± 1.07, and 3.28 ± 1.25 during right excursion; and 1.88 ± 0.99, 2.08 ± 1.11, 2.07 ± 0.68, and 3.01 ± 1.53 during protrusion. When compared to Class I and Class II malocclusions, Class III showed a significantly higher mean DT of each excursion (p < 0.05).Conclusion Class III had the significantly highest mean DT of each excursion and the significantly longest DT in all excursions.
Keywords: Angle’s malocclusions; disclusion time; T-Scan III